2017
DOI: 10.1097/fpc.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme insertion/deletion gene polymorphism and interferon-β treatment response in multiple sclerosis patients

Abstract: We investigated the effect of the functional insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene on the response to interferon-β (IFN-β) therapy in Croatian and Slovenian patients with multiple sclerosis (MS). A total of 275 IFN-β treated MS patients [162 responders (Rs) and 113 nonresponders (NRs)] were genotyped by PCR. The ACE I/D genotype distribution and allele frequencies did not differ between female Rs and NRs. However, male NRs tended to have a greater prevalence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the past 15 years, our study groups have been investigating the possible relevance of the ACE1 I/D polymorphism in various diseases and/or conditions in the Croatian population. Most of our studies suggest that the ACE1 D allele as well as the ACE1 D/D genotype may be risk factors in multiple sclerosis, 7 , 8 schizophrenia, 9 and lung cancer. 10 Importantly, we have also found that the risk effects of the ACE1 D allele and ACE1 D/D genotype were in general more prominent among male patients with multiple sclerosis 7 , 8 and schizophrenia.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In the past 15 years, our study groups have been investigating the possible relevance of the ACE1 I/D polymorphism in various diseases and/or conditions in the Croatian population. Most of our studies suggest that the ACE1 D allele as well as the ACE1 D/D genotype may be risk factors in multiple sclerosis, 7 , 8 schizophrenia, 9 and lung cancer. 10 Importantly, we have also found that the risk effects of the ACE1 D allele and ACE1 D/D genotype were in general more prominent among male patients with multiple sclerosis 7 , 8 and schizophrenia.…”
mentioning
confidence: 86%
“…Most of our studies suggest that the ACE1 D allele as well as the ACE1 D/D genotype may be risk factors in multiple sclerosis, 7 , 8 schizophrenia, 9 and lung cancer. 10 Importantly, we have also found that the risk effects of the ACE1 D allele and ACE1 D/D genotype were in general more prominent among male patients with multiple sclerosis 7 , 8 and schizophrenia. 9 Indeed, COVID-19 infection has previously been associated with sex, 11 and a recent article discussing the angiotensin-converting enzyme 2 (encoded by the ACE2 gene), which has been known to cooperate with ACE1 in the renin–angiotensin system, hypothesizes that sex differences in COVID-19 severity may be related to the ACE1 and ACE2 genes.…”
mentioning
confidence: 86%
“…ACE polymorphism may influence the serum level of ACE. A functional insertion/deletion (I/D) polymorphism in the ACE gene has been recognized (Ristic et al, 2017). The ACE insertion/deletion (I/D) polymorphism is based on a 287bp Alu repeat sequence within intron 16 (Gong et al, 2012;Yigit et al, 2013).…”
Section: )mentioning
confidence: 99%